(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE METHODOLOGY To determine a comparative assessment between rectal delivery of diclofenac sodium and indomethacin regarding their ability to prevent PEP. Researchers conducted a prospective observation study within PNS Shifa Hospital of Karachi during the period from November 2024 to February 2025. The researchers divided their patient sample into groups of 100 participants undergoing ERCP. Each group received different pain medications either as rectal diclofenac or rectal indomethacin 30 minutes before starting the procedure. The main study goal was determining PEP incidence through new abdominal pain followed by serum amylase or lipase levels which exceeded the upper normal range during the post-procedure twenty-four period. The evaluation included PEP severity and ERCP complications together with hospital stay duration and adverse effects of medications. RESULTS A larger number of patients (10%) developed PEP after diclofenac administration but this result did not achieve statistical significance (p=0.332) compared to the indomethacin-treated group (16%). The PEP severity levels between these groups paralleled one another since both groups showed equal rates of mild to moderate pancreatitis cases. Severe pancreatitis cases failed to appear during any phase of the study. All groups experienced similar minimal rates of complications as well as adverse effects related to ERCP procedures. CONCLUSION The incidence of PEP declined effectively when patients received diclofenac or indomethacin yet diclofeanc showed a marginally lower rate of PEP. The safety profiles of diclofenac and indomethacin are comparable so both drugs can serve for routine prophylaxis although additional large-scale randomized studies need to create definitive recommendations.